Bibliometric and visualized analysis of scientific publications on rehabilitation of rotator cuff injury based on web of science - Hu, Yu; Wu, Linfeng; He, Lin; Luo, Xiaozhou; Hu, Linzhe; Wang, Yuchan; Zhao, Xin (Frontiers in Public Health, 2023)
Background: Since the discovery of rehabilitation as an intervention for rotator cuff injury, its impact on the recovery of rotator cuff injury has attracted crucial attention, and the number of related studies is increasing worldwide. There were no bibliometric and visualized analysis studies in this field. This study aimed to investigate the research hotpots and trends in rehabilitation of rotator cuff injury via bibliometric and visualized analysis and to identify the future development of clinical practice. Method: The publications regarding rehabilitation of rotator cuff injury from inception to December 2021 were obtained from the Web of Science Core Collection database. The trends of publications, co-authorship and co-occurrence analysis and visualized analysis were carried out using Citespace, VOSviewer, Scimago Graphica software and R Project. Results: a total of 795 publications were included in this study. The number of publications significantly increased yearly. The United States published the highest number of related papers and the papers published by the United States had the highest citations. The University of Laval, the University of Montreal and Keele University were the top 3 most contributive institutions. Additionally, the Journal of Shoulder and Elbow Surgery was the journal with the highest number of publications. The most common keywords were “rotator cuff”, “rehabilitation”, “physical therapy”, “management”, and “telerehabilitation”. Conclusion: The total number of publications has shown a steady upward trend. the cooperation between countries globally was still relatively lacking, and therefore it is necessary to strengthen cooperation between different countries and regions to provide conditions for multi-center, large sample and high-quality research. In addition to the relatively mature rehabilitation of RCI such as passive motion or exercise therapy, telerehabilitation has also attracted much attention with the progress of science.